Mineralogical and Geochemical Discrimination of the Occurrence and Genesis of Palygorskite in Eocene Sediments on the Northeastern Tibetan Plateau. (1st March 2018) - Ye, Chengcheng; Yang, Yibo; Fang, Xiaomin; Hong, Hanlie; Zhang, Weilin; Yang, Rongsheng; Song, Bowen; Zhang, Zhiguo
Abstract: Palygorskite is a widely used indicator of semiarid to arid environments in paleoclimate studies. In this study, we present detailed mineralogical and geochemical investigations exploring the genesis of palygorskite found in Eocene fluvial sediment in the northern Qaidam Basin on the northeastern Tibetan Plateau. The presence of two types of palygorskite is revealed, based on their crystallinity characteristics and distinctive rare earth element (REE) patterns in the coexisting clay fraction. Well‐crystallized palygorskite samples are characterized by remarkably negative Ce anomalies and obvious middle rare earth element enrichment. Poorly crystallized palygorskite samples generally exhibit positive Ce anomalies and less pronounced middle rare earth element enrichment, which resemble those of nonpalygorskite‐bearing clay samples. Given the presence of an overall oxidized fluvial sedimentary environment, we attribute the well‐crystallized palygorskite (which has textures comprising long, interwoven fibers) to direct precipitation (i.e., neoformation) occurring within a reducing environment during early/postdepositional processes while the poorly crystallized palygorskite (which is characterized by short, club‐shaped single crystals) originates as catchment‐delivered detritus. These poorly crystallized palygorskites occur mostly in 49.5–47.0 Ma and are accompanied by decreasing kaolinite content, increasing chlorite content, and abundant xerophytic spore‐pollen from the Qaidam Basin, and its neighboring Xining Basin. Collectively, these evidences suggest that a less humid climate followed after the Early Eocene Climate Optimum. Key Points: Two different palygorskite types in Eocene fluvial sediments in the Qaidam Basin Well‐crystallized palygorskite formed during postdeposition while poorly crystallized palygorskite is catchment‐delivered detritus Poorly crystallized palygorskite suggests a less humid climate after the Early Eocene Climate Optimum